New Directions in Mantra Studies: Exploring the Emergence of Mantra Repetition - Haas, Dominik A. (AЯGOS, 2025)
Many theories understand repetitiveness to be inherent in the concept of mantra itself. Despite its popularity and its significance for South Asian - and, indeed, global—religious history, mantra repetition has been insufficiently defined as an object of research. The peculiarities of the repetitiveness of mantra repetition are hardly ever reflected upon in academic literature. Furthermore, it has been assumed that mantra repetition is a timeless and even universal practice. Consequently, mantra repetition has eluded adequate scholarly analysis: Significant terminological particularities in primary sources have been overlooked and the possibility of historical developments has not been considered. In this article, I survey the current state of research relevant for the study of the emergence of mantra repetition - in particular, the practice of continuously reciting one and the same short formula - from its post-Vedic origins up to the middle of the first millennium CE. I also formulate research questions and hypotheses to guide future studies on the subject.